2015
DOI: 10.1007/s40495-015-0019-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Anti-cancer Properties of β-Escin, a Triterpene Saponin

Abstract: Horse chestnut seed extract is well known for its antiedematous and anti-inflammatory medicinal properties. More recently, potential anti-carcinogenic properties have been described. β-Escin, a pentacyclic triterpene saponin with aglycone moieties, is the main active compound in horse chestnut seed extract. Here, we summarize the anti-cancer properties of β-escin in preclinical models, and its potential pharmacological use as an anti-inflammatory agent for the treatment of edema and chronic venous insufficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…In traditional Chinese medicine, Escin has been widely used to promote appetite, prevent gas formation of gastrointestinal tract, and documented as an antiseptic, anti‐edematous, and anti‐inflammatory agent in various disease models . Studies have shown the major mechanisms for the anti‐inflammatory effects of Escin are through modulation of NF‐ κ B signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In traditional Chinese medicine, Escin has been widely used to promote appetite, prevent gas formation of gastrointestinal tract, and documented as an antiseptic, anti‐edematous, and anti‐inflammatory agent in various disease models . Studies have shown the major mechanisms for the anti‐inflammatory effects of Escin are through modulation of NF‐ κ B signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Unless otherwise noted, all data presented as n (%).The disease control rate was defined as the proportion of patients who had a best response rating of a complete response, partial response, or stable disease that was maintained for ≥4 weeks from the first manifestation of the rating. gastrointestinal tract, and documented as an antiseptic, anti-edematous, and anti-inflammatory agent in various disease models [29]. Studies have shown the major mechanisms for the anti-inflammatory effects of Escin are through modulation of NF-κB signaling pathway [29].…”
Section: Variablementioning
confidence: 99%
“…Escin, or aescin, a natural mixture of triterpene saponins, is the major active compound in extracts from the seeds of Aesculus hippocastanum (horse chestnut tree), a widely used medicinal plant since ancient times910. It exists in two forms, α and β and the latter is the active component of the mixture10.…”
mentioning
confidence: 99%
“…It exists in two forms, α and β and the latter is the active component of the mixture10. Escin has been traditionally used as a carminative, stomachic, and endothelia-protective agent in treating peripheral vascular disorders, in particular varicosis11.…”
mentioning
confidence: 99%
See 1 more Smart Citation